Plant growth promoting rhizobacteria and biochar production from Parthenium hysterophorus enhance seed germination and productivity in barley under drought stress - Gul, Farrukh; Khan, Irfan Ullah; Rutherford, Susan; Dai, Zhi-Cong; Li, Guanlin; Du, Dao-Lin (Frontiers in Plant Science, 2023)
Drought stress can significantly affect plant growth and development. Biochar (BC) and plant growth-promoting rhizobacteria (PGPR) have been found to increase plant fertility and development under drought conditions. The single effects of BC and PGPR in different plant species have been widely reported under abiotic stress. However, there have been relatively few studies on the positive role of PGPR, BC, and their combination in barley (Hordeum vulgare L.). Therefore, the current study investigated the effects of BC from Parthenium hysterophorus, drought tolerant PGPR (Serratia odorifera), and the combination of BC + PGPR on the growth, physiology, and biochemical traits of barley plants under drought stress for two weeks. A total of 15 pots were used under five treatments. Each pot of 4 kg soil comprised the control (T0, 90% water), drought stress alone (T1, 30% water), 35 mL PGPR/kg soil (T2, 30% water), 2.5%/kg soil BC (T3, 30% water), and a combination of BC and PGPR (T4, 30% water). Combined PGPR and BC strongly mitigated the negative effects of drought by improving the shoot length (37.03%), fresh biomass (52%), dry biomass (62.5%), and seed germination (40%) compared to the control. The PGPR + BC amendment treatment enhanced physiological traits, such as chlorophyll a (27.9%), chlorophyll b (35.3%), and total chlorophyll (31.1%), compared to the control. Similarly, the synergistic role of PGPR and BC significantly (p< 0.05) enhanced the antioxidant enzyme activity including peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD) to alleviate the toxicity of ROS. The physicochemical properties (N, K, P, and EL) of the soils were also enhanced by (85%, 33%, 52%, and 58%) respectively, under the BC + PGPR treatment compared to the control and drought stress alone. The findings of this study have suggested that the addition of BC, PGPR, and a combination of both will improve the soil fertility, productivity, and antioxidant defense systems of barley under drought stress. Therefore, BC from the invasive plant P. hysterophorus and PGPR can be applied to water-deficient areas to improve barley crop production.